Chemogenetic stimulation of adult neurogenesis, and not neonatal neurogenesis, is sufficient to improve long-term memory accuracy. (December 2022) - Lods, Marie; Mortessagne, Pierre; Pacary, Emilie; Terral, Geoffrey; Farrugia, Fanny; Mazier, Wilfrid; Masachs, Nuria; Charrier, Vanessa; Cota, Daniela; Ferreira, Guillaume; Abrous, Djoher Nora; Tronel, Sophie
Abstract: Hippocampal adult neurogenesis is involved in many memory processes from learning, to remembering and forgetting. However, whether or not the stimulation of adult neurogenesis is a sufficient condition to improve memory performance remains unclear. Here, we developed and validated, using ex-vivo electrophysiology, a chemogenetic approach that combines selective tagging and activation of discrete adult-born neuron populations. Then we demonstrated that, in rats, this activation can improve accuracy and strength of remote memory. These results show that stimulation of adult-born neuron activity can counteract the natural fading of memory traces that occurs with the passage of time. This opens up new avenues for treating memory problems that may arise over time. Highlights: Memory quality fades with the passage of time and accuracy declines. Chemogenetic stimulation of hippocampal adult-born neurons can restore memory accuracy. Stimulation of neurons generated before learning and not neonatally can improve long-term memory.